Exploring the influence of Sternberg's thinking styles on students' mathematical creative problem-solving - Noviani, Julia; Ahmad, Nurul Qomariyah; Dewi, Indah Puspita; Ulfa, Mahfudzah (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
Creative thinking is an essential skill for students in the 21st century, especially in mathematics, requiring problem-solving and analytical abilities. This study aims to analyze the creative thinking abilities of high school students in solving mathematical problems, analyzed through Sternberg’s legislative, executive, and judicial thinking styles. A mixed method approach was employed, combining quantitative analysis of thinking style questionnaires and mathematics ability tests with qualitative examination of students’ creative thinking task responses and interview data. Nine students were purposively selected from the 37 participants for in-depth analysis based on their dominant thinking styles and mathematical ability levels. These students were analyzed further through their written responses and semi-structured interviews to gain deeper insights into their mathematical creative thinking processes. Students completed a mathematical creative thinking task, evaluated on four indicators: fluency, flexibility, originality, and elaboration. Findings revealed that all students were categorized at MCT Level 2 (Quite Creative), demonstrating only partial fluency and elaboration. No subject fulfilled flexibility or originality criteria, indicating limited strategic and novel thinking across styles. Interestingly, students with low mathematical ability also reached MCT Level 2, suggesting that creative thinking can be independent of academic performance. Legislative students lacked strategic variation despite their preference for autonomy, executive students relied strictly on procedural methods, and judicial students remained evaluative but unoriginal. Future research should involve a larger and more diverse sample to explore broader dimensions of students’ cognitive processes in mathematical learning. These findings imply that differentiated instruction based on thinking styles may be key to cultivating creativity in mathematics classrooms. The study underscores the need for instructional approaches emphasizing divergent thinking and creative exploration to align with diverse cognitive styles and enhance students' mathematical creativity.